In Defense of Statics - Boulding, K. E. (Quarterly Journal of Economics, 1955)
I. Statics and dynamics — their nature and uses, 485. — II. Simple model of exponential growth, 488. — III. Models of population growth, 489. — IV. Accelerator-multiplier models, 490. — V. The Harrod-Domar-Hicks dynamic model, 492. — VI. Systems of economic development, 495. — VII. Possible avenues of escape from the rigidity of the dynamic model, 498. — VIII. Appraisal of comparative statics, 499. — IX. Conclusion, 501.